2015
DOI: 10.1253/circj.cj-14-1059
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification in Patients With Brugada Syndrome Without Previous Cardiac Arrest

Abstract: 310OKAMURA H et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 23 publications
1
26
0
2
Order By: Relevance
“…The authors concluded that VT/VF inducibility is not sufficient to identify high-risk patients, whereas the presence of a spontaneous type I ECG, history of syncope, ventricular effective refractory period less than 200 ms, and QRS fragmentation are useful for identification of candidates for a prophylactic ICD. Recently, Okamura et al 26 published a retrospective study regarding BrS patients. The authors concluded that syncope, spontaneous type I Brugada ECG, and positive programmed electrical stimulation are important risk factors for SCD and VF in patients with BrS but without previous cardiac arrest.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…The authors concluded that VT/VF inducibility is not sufficient to identify high-risk patients, whereas the presence of a spontaneous type I ECG, history of syncope, ventricular effective refractory period less than 200 ms, and QRS fragmentation are useful for identification of candidates for a prophylactic ICD. Recently, Okamura et al 26 published a retrospective study regarding BrS patients. The authors concluded that syncope, spontaneous type I Brugada ECG, and positive programmed electrical stimulation are important risk factors for SCD and VF in patients with BrS but without previous cardiac arrest.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…8, 33 Putatively, the diurnal change of T-wave morphology in patients with hypertrophic cardiomyopathy 34 might explain the inappropriate shock due to T-wave oversensing, which cannot be detected on screening ECG alone. Patients with Brugada syndrome at high risk of VF should also be considered for S-ICD implantation (give their young age), 35 but the clinician should be aware that a positive ST-T segment change in precordial leads during class I blockade has been reported to indicate failure for S-ICD on screening ECG. 36 Careful when infections occur in patients with S-ICD, they have not resulted in sepsis (a particularly threatening condition in congenital patients with conduits and/or prosthetic valves), because the entire system is extravascular.…”
Section: Inverted T Wave In Precordial Lead As Predictor Of Screeningmentioning
confidence: 99%
“…We excluded cases with syncope that was likely due to vasovagal events, such as those that occurred during abrupt postural changes, exposure to heat and dehydration, or emotional reactions. 10) A family history of syncope was defined as an episode of sudden death that was judged as likely being caused by ventricular arrhythmia.…”
Section: Methodsmentioning
confidence: 99%